UINSU Students' Understanding of Aurat and Shar'i Clothing in the Qur'an Surah An-Nur verse 31 and Surah Al-Ahzab verse 59 - Aritonang, Pebrina Yanti; Is, Fadhillah (QiST: Journal of Quran and Tafseer Studies, 2025)
This study examines the understanding of students at the State Islamic University of North Sumatra (UINSU) regarding aurat and sharia-compliant clothing as outlined in QS. An-Nur: 31 and QS. Al-Ahzab: 59. Employing a qualitative approach with a phenomenological method, the research explores the subjective experiences of 20 students from diverse faculties through in-depth, semi-structured interviews. Findings reveal that while most students possess a general awareness of Aurat boundaries, only a few can articulate the relevant Qur'anic arguments in detail. The practice of wearing sharia-compliant clothing is predominantly shaped by social influences-such as peer dynamics, campus culture, and digital media exposure-rather than a deep textual understanding of the verses. Social media functions as a contested space: it simultaneously serves as a vehicle for Islamic outreach (Da'wah) and as a channel for aesthetic fashion trends, often leading to ambivalence in religious expression. Thematic analysis identifies three core factors influencing students' clothing practices: religious education, social norms within the campus environment, and digital media influence. This study underscores the urgency of a contextual and integrative Islamic educational framework-grounded in Maqashid Shariah-to cultivate an ethical, reflective, and substantive awareness of Islamic dress among contemporary Muslim students.